Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.2307/3870656
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis bZIP Protein HY5 Directly Interacts with Light-Responsive Promoters in Mediating Light Control of Gene Expression

Abstract: The Arabidopsis HY5 gene has been defined genetically as a positive regulator of photomorphogenesis and recently has been shown to encode a basic leucine zipper type of transcription factor. Here, we report that HY5 is constitutively nuclear localized and is involved in light regulation of transcriptional activity of the promoters containing the G-box, a well-characterized light-responsive element (LRE). In vitro DNA binding studies suggested that HY5 can bind specifically to the G-box DNA sequences but not to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
116
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(125 citation statements)
references
References 0 publications
9
116
0
Order By: Relevance
“…These results show that the expression of the ZGT gene is light inducible and further suggest that the regulation of its photoresponsiveness occurs at least partially via changes in transcriptional rates. These results are consistent with the hypothesis that the G/E box in the ZGT promoter is recognized by light-regulated transcription factors such as PIF3 (Martínez-García et al, 2000) and HY5 (Chattopadhyay et al, 1998).…”
Section: Expression Of the Zgt Gene Is Light Regulated And Light Depesupporting
confidence: 91%
See 2 more Smart Citations
“…These results show that the expression of the ZGT gene is light inducible and further suggest that the regulation of its photoresponsiveness occurs at least partially via changes in transcriptional rates. These results are consistent with the hypothesis that the G/E box in the ZGT promoter is recognized by light-regulated transcription factors such as PIF3 (Martínez-García et al, 2000) and HY5 (Chattopadhyay et al, 1998).…”
Section: Expression Of the Zgt Gene Is Light Regulated And Light Depesupporting
confidence: 91%
“…Phytochrome B binds reversibly to G-box-bound PIF3 upon light-triggered conversion of phytochrome B to its biologically active conformer. A similar story has been reported for the bZIP protein factor, HY5 (Chattopadhyay et al, 1998). The presence in the ZGT promoter of this core G-box element for light signaling is consistent with a role in the light regulation of ZGT by PIF3 and/or HY5.…”
Section: Light-and Clock-regulated Motifs In the Zgt Promotersupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, we evaluated the drought resistance of 14 transgenic Arabidopsis-overexpressing PYLs driven by the constitutive 35S cauliflower mosaic virus (CaMV) promoter, the stress-inducible RD29A promoter, the guard cell-specific GC1 and ROP11 promoters (20,21), and the green tissue-specific ribulose bisphosphate carboxylase small subunit (RBCS) RBCS-1A promoter (22). We found that, relative to the WT and all other combinations, pRD29A::PYL9 transgenic Arabidopsis plants had both greater drought resistance and accelerated drought-or ABA-induced leaf senescence.…”
Section: Significancementioning
confidence: 99%
“…The HY5 locus encodes a bZIP transcription factor known to be important for deetiolation and expression of several genes related to photosynthesis. In Arabidopsis the HY5 protein binds to Light Responsive Elements (LRE) in promoters, for instance a Gbox (Chattopadhyay et al 1998). HY5 degradation is stimulated by another protein, COP1.…”
Section: Nr Promoters and Light Regulationmentioning
confidence: 99%